2002
DOI: 10.1104/pp.010508
|View full text |Cite
|
Sign up to set email alerts
|

AtFXG1, an Arabidopsis Gene Encoding α-l-Fucosidase Active against Fucosylated Xyloglucan Oligosaccharides

Abstract: An ␣-l-fucosidase (EC 3.2.1.51) able to release the t-fucosyl residue from the side chain of xyloglucan oligosaccharides has been detected in the leaves of Arabidopsis plants. Moreover, an ␣-l-fucosidase with similar substrate specificity was purified from cabbage (Brassica oleracea) leaves to render a single band on SDS-PAGE. Two peptide sequences were obtained from this protein band, and they were used to identify an Arabidopsis gene coding for an ␣-fucosidase that we propose to call AtFXG1. In addition, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The AXY8-GFP fusion was present in the apoplast and was retained in the apoplast when the plasma membrane, as indicated by the marker FM 4-64, receded under plasmolysis-inducing conditions ( Figure 3J; see Supplemental Figure 5 online). These experiments confirmed earlier reports that AXY8 represents a soluble protein (Lé onard et al, 2008) and that plant fucosidase activities can be found in apoplastic extracts of plants (de la Torre et al, 2002;Franková and Fry, 2011).…”
Section: Axy8 Encodes a Ubiquitously Expressed Apoplastic Xyg: A-fucosupporting
confidence: 81%
See 2 more Smart Citations
“…The AXY8-GFP fusion was present in the apoplast and was retained in the apoplast when the plasma membrane, as indicated by the marker FM 4-64, receded under plasmolysis-inducing conditions ( Figure 3J; see Supplemental Figure 5 online). These experiments confirmed earlier reports that AXY8 represents a soluble protein (Lé onard et al, 2008) and that plant fucosidase activities can be found in apoplastic extracts of plants (de la Torre et al, 2002;Franková and Fry, 2011).…”
Section: Axy8 Encodes a Ubiquitously Expressed Apoplastic Xyg: A-fucosupporting
confidence: 81%
“…Two Arabidopsis genes have been proposed to encode XyG: fucosidases: FXG1, as it exhibits a-fucosidase activity against XyG oligosaccharides when heterologously expressed (de la Torre et al, 2002), and Fuc95A that when expressed heterologously as previously shown is able to release Fuc from XyG oligosaccharides and polymers (Lé onard et al, 2008). However, their role in planta has not been established yet.…”
Section: Axy8 a Dominant Apoplastic Acting Xyg:a-fucosidasementioning
confidence: 99%
See 1 more Smart Citation
“…Any change in the side-chain structures of xyloglucan may result primarily from a net change in biosynthesis, production of the substrate (GDP-Fuc) by fucosyltransferases, or catabolism by fucosidases. A number of enzymes affecting xyloglucan side chains have been identified: MUR1/GMD1, GMD2, and GER are involved in the synthesis of GDP-Fuc (Bonin and Reiter, 2000); MUR2 is a xyloglucan-specific fucosyltransferase (Perrin et al, 1999); MUR3 is a galactosyl transferase, catalyzing the addition of Gal to the third position of XXXG but not to the equivalent position of XLXG (Madson et al, 2003); and FXG1 is a fucosidase that removes fucosyl moieties from XyGOs (De La Torre et al, 2002). Neither MUR2 nor any of the other nine members of the fucosyltransferase gene family map to any of the three QTL.…”
Section: Complex Control Of Xyloglucan Side-chain Modificationmentioning
confidence: 99%
“…Crystal structural studies have shown that GH29 enzymes have a conserved catalytic active site formed at one end of a (␤/␣) 8 triosephosphate isomerase (TIM) barrel domain, whereas GH95 enzymes have their active site formed by an (␣/␣) 6 helical barrel domain (22,23,(27)(28)(29). Besides GH29 and GH95 enzymes, A. thaliana also expresses a novel lipase-like fucosidase named AtFXG1, which has not been classified in CAZy (33).…”
mentioning
confidence: 99%